Introduction to wavefront sensors - Geary, Joseph M. (SPIE Optical Engineering Press, 1995)
This is a practical book on wavefront sensing. Emphasis is on principles and techniques, rather than detailed mathematical analysis of such systems. The goal is to provide the reader with a qualitative understanding of wavefront sensor operation.
Keywords: Holography.; Optical detectors.; Optics, Adaptive.; elektronické knihy; electronic books